ESPAÇAMENTO ENTRE LINHAS E FONTES DE ADUBAÇÃO NITROGENADA EM CANOLA - Noronha, Uelinton; Kruger, Cleusa A. M. B.; Silva, Jose A. G. d.; Matter, Edegar; Silva, Adair J. d.; Viera, Rogério; Fontaniva, Cristiano; Mattioni, Tânia; Antonow, Diovani; Bandeira, Taiane P. (Salão do Conhecimento, 2013)
Resumo